Adjunct Analgesia Reduces Pain and Opioid Consumption After Hip Arthroscopy: A Systematic Review of Randomized Controlled Trials. Issue 14 (December 2020) - Kunze, Kyle N.; Polce, Evan M.; Lilly, Daniel T.; Garcia, Flavio L.; Cohn, Matthew R.; Nho, Shane J.; Chahla, Jorge
Background: Patients who undergo hip arthroscopy inevitably experience pain postoperatively; however, the efficacy and safety of adjunct analgesia to prevent or reduce pain are not well-understood. Purpose: To perform a comprehensive qualitative synthesis of available randomized controlled trials evaluating the effect of adjunct analgesia on postoperative (1) pain, (2) opioid use, and (3) length of stay (LOS) in patients undergoing hip arthroscopy. Study Design: Systematic review. Methods: PubMed, OVID/MEDLINE, and Cochrane Controlled Register of Trials were queried for studies pertaining to analgesia interventions for patients undergoing hip arthroscopy. Two authors independently assessed article bias and eligibility. Data pertaining to changes in pain scores, additional analgesia requirements, length of hospital stay, and complications were extracted and qualitatively reported. Network meta-analyses were constructed to depict mean pain, opioid use, and LOS among the 3 analgesia categories (blocks, local infiltration analgesia, and celecoxib). Results: Fourteen level 1 studies were included; 12 (85.7%) reported pain reductions in the immediate and perioperative period after hip arthroscopy. Of the 7 studies that assessed an intervention (2 celecoxib, 1 fascia iliaca block, 1 lumbar plexus block, 1 femoral nerve block, 1 intra-articular bupivacaine, 1 extracapsular bupivacaine) versus placebo, more than half reported that patients who received an intervention consumed significantly fewer opioids postoperatively than patients who received placebo (lowest P value = .0006). Of the same 7 studies, 2 reported significantly shortened LOS with interventions, while 4 reported no statistically significant difference in LOS and 1 did not report LOS as an outcome. Conclusion: The majority of studies concerning adjunct analgesia for patients undergoing hip arthroscopy suggest benefits in pain reduction early in the postoperative period. There is mild evidence that adjunct analgesia reduces postoperative opioid use and currently inconclusive evidence that it reduces length of hospital stay. Furthermore, it appears that local infiltration analgesia may provide the greatest benefits in reductions in pain and opioid consumption. We recommend the use of adjunct analgesia in appropriately selected patients undergoing hip arthroscopy without contraindication who are at a high risk of severe postoperative pain.